NPUST Sustainable Operations and the Development of Circular Economies - H, Tai; P.M, Li (Journal of Sustainability Perspectives, 2021)
The National Pingtung University of Science and Technology was established as an agricultural institution in 1924. With a true appreciation for the environment, the university is dedicated to the pursuit of technology and practices that are sustainable, eco-friendly and environmentally sound. The university has already earned a reputation for “being Green” as a result of its approach to sustainable operations and circular economies. The university is actively working to make its campus Greener and healthier through simple measures, such as lending out free bicycles to students, and complex measures, such as developing water treatment and recycling systems designed to conserve water and restore eco-systems. Additionally, the university is working to raise environmental awareness among its students and is actively investing in the research and development of technologies that will be able to help businesses operate more sustainably in the future.